D'où vient l'emploi ? Marché, État et action collective - Tremblay, Diane-Gabrielle (Relations Industrielles / Industrial Relations, 2015)
The article reviews the book, "D'où vient l'emploi ? Marché, État et action collective" by Frédéric Hanin.
Keywords: D'OU vient l'emploi? Marche; Etat et action collective (Book); HANIN; Frederic; Industrial relations; LABOR market; Nonfiction